The 'Annals' of Flodoard of Reims, 919-966 - Bachrach, Bernard S., 1939-; Bachrach, Bernard S., 1939-; Fanning, Steven; Fanning, Steven (Book collections on Project MUSE., 2011)
"This is a very welcome addition to an excellent series. Fanning and Bachrach make this important and hitherto rather neglected text accessible for the first time in an admirably clear translation."--Rosamond McKitterick, University of Cambridge.